DESIGN OF AN ERP-BASED INTEGRATED INFORMATIONSYSTEM FOR HEALTH DATA MANAGEMENT ATLUBUKLINGGAU HEALTH AGENCY - Yuda Pratama Wibawa; Feby Charlos (LPPM Unbaja, 2026)
This research focuses on the design and development of an integrated ERP (Enterprise Resource Planning)-based information system for managing health data at the Lubuklinggau City Health Agency. The key issue addressed is the fragmented nature of health data management and the absence of an integrated system within local government agencies. Inadequate integration of health data can lead to inefficiencies, errors, and delayed decision-making, which impacts public health services. This study identifies the core challenges related to the inefficiency and inaccuracy of health data management at the local government level. The research employs a system design methodology combined with a qualitative approach. It begins with an in-depth user needs analysis to understand the specific requirements of the Health Agency. Based on this analysis, an ERP model is developed, focusing on integrating various health data management functions such as patient information, financial records, and health statistics into a unified system. The system is designed to improve data accuracy, streamline operations, and facilitate real-time reporting, contributing to more informed decision-making. The expected outcome is the creation of a functional ERP-based system that enhances the integration and efficiency of health data management at the Lubuklinggau City Health Agency. This research provides practical solutions for overcoming current data management challenges, offering a model that can be replicated by other local health agencies. Furthermore, it introduces an innovative ERP approach to the public health sector, demonstrating its potential to improve both the operational effectiveness and service delivery in local government health departments. This research significantly contributes to advancing health information systems by integrating ERP solutions into public sector health management.